Preparing middle level educators for 21st century schools : enduring beliefs, changing times, evolving practices - Howell, Penny B.; Faulkner, Shawn A.; Jones, Jeanneine P.; Carpenter, Jan Marie (Handbook of research in middle level education series., 2018)
"The research presented in this volume is organized into three sections, with an introduction provided for each. The authors grounded their work in the Association for Middle Level Education's teacher preparation standards (2012) and tenets of This We Believe (NMSA, 2010). By doing so, they examine topics that hold potential for meeting the learning needs of teachers and students in middle level schools. The first section includes chapters from individuals working to ensure that the enduring beliefs of middle level education continue to guide the structures of their middle level teacher preparation programs. The second set of chapters closely examines how changing times are shaping the work of teacher educators. Finally, the last section spotlights evolving practices that continue to develop in response to the changes impacting our classrooms, schools, and communities. This text provides readers with researched-based practices and information to help them continue the tradition of middle level teacher education. The enduring beliefs of preparing teachers who understand, respect, and honor the many talents, gifts, and contributions of the young adolescent student will guide teacher educators as they respond to the changing times of education and the evolving practices of teachers, teacher educators, and schools"--